Aplicação da combinação melaço-calcário em tanques de criação de Juvenis de Tilápia do Nilo, Oreochromis niloticus - Apoliano, Marcos Luiz da Silva (2021)
The work aimed to analyze the effects of applying different combinations between liquid molasses and agricultural limestone, on water quality and zootechnical performance of juvenile Nile tilapia, Oreochromis niloticus. The study used 24 tanks of 100 L, in an indoor cultivation system, and 24 tanks of 250 L, in an outdoor cultivation system. Four control groups were constituted (no product applied, only molasses, only limestone, molasses-limestone mixture without fish) and two experimental groups (molasses-limestone mixture with ≈ 32% and 48% molasses), with four replicates each. Over eleven weeks, systematic monitoring of the water quality of the tanks was carried out. The nictimeral monitoring of O2, temperature, pH, electrical conductivity and total alkalinity, in addition to the determination of chlorophyll a, in outdoor tanks was carried out at the end of the 8th week. The combination of molasses to limestone accelerated the rate of dissolution of limestone in water. The mixture containing 48% molasses promoted greater elevations in alkalinity and pH of water, in relation to tanks with application of only limestone. Despite these benefits, an application the molasses-limestone combination impaired the zootechnical performance of juvenile tilapia, especially in outdoor tanks. It was concluded that the application of molasses-limestone combination should not be carried out in fish breeding tanks that have a preference for life in more acidic waters, such as Nile tilapia.